Analisa Persaingan Bisnis Antara Merek Mie Sedap Dan Mie Indomie - Anneira Azzahra; Mia Mulyani Zahra; Syamsul Hidayat (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2024)
People's lives have begun to change in this era of globalization, everything that is needed is required to be fast and practical. Several needs, including food, have become instantaneous, creating a very high level of development in the food business, especially in Indonesia. . With the current busy activities of society, business actors have the opportunity to create fast food products (Hernawan, 2019). Therefore, new businesses began to emerge known as fast food or fast food. Instant noodles are popular with everyone, both young and old. Therefore, the focus of the research entitled "BUSINESS COMPETITION ANALYSIS BETWEEN SEDAP NOODLE AND INDOMIE NOODLE BRAND" focuses on when purchasing a product, there are many factors that consumers consider to make a decision. In addition to the economic situation of each consumer. The method used in this research is quantitative or statistical. Quantitative research methods are methods used for research on certain populations or samples and are based on the philosophy of empiricism. Thus, this approach will allow analysts to find out the extent of business competition between the Sedap noodle and Indomie noodle brands among Bina Bangsa University Serang students. People currently choose instant noodles because they are cheap, easy to prepare and long-lasting (Cindy et al. , 2016). Currently, many companies competing in the instant noodle business make various different variations, providing superior products to offer to the public by producing instant noodle products such as Sedaap noodles, Indomie, Supermie, Sarimi, Gaga noodles, ABC, Success noodles and others. (Roisah et al., 2021). However, instant noodle products are currently very vulnerable to brand switching because many new products have emerged with new flavor variants, resulting in consumers switching brands for certain reasons (Indrawati & Untarini, 2017).